Association between the Degree of Twin Birthweight Discordance and Perinatal Outcomes - Kim, Lena H.; Caughey, Aaron B.; Yee, Lynn M.; Cheng, Yvonne W. (American Journal of Perinatology, 2019)
Background Twin birthweight discordance is associated with adverse outcomes.Objective To determine what degree of twin birthweight discordance is associated with adverse outcomes.Study Design This is a retrospective cohort study of twins with vertex twin A delivered vaginally at 36 to 40 weeks (U.S. Vital Statistics Natality birth certificate registry data 2012–2014). The primary outcome was a composite of neonatal morbidity: 5-minute Apgar < 7, neonatal intensive care unit admission, neonatal mechanical ventilation > 6 hours, neonatal seizure, and/or neonatal transport to a higher level of care. Effect estimates were expressed as incidence rate and adjusted odds ratio (aOR) controlling for confounding using multivariate clustered analysis for between-pair effects, and multilevel random effect generalized estimating equation regressions to account for within-pair effects. We adjusted for sex discordance, breech delivery of the second twin, maternal race/ethnicity, nulliparity, age, marital status, obesity, and socioeconomic status.Results In comparison to birthweight discordance of ≤20%, aORs with 95% confidence intervals (CIs) by weight discordance of the primary outcome among 27,276 twin deliveries were as follows: 20.01 to 25% (aOR: 1.46 [95% CI: 1.29–1.65]); 25.01 to 30% (aOR: 1.96 [95% CI: 1.68–2.29]); and 30.01 to 60% (aOR: 2.97 [95% CI: 2.52–3.50]).Conclusion Twin birthweight discordance >20% was associated with increased odds of adverse neonatal outcome.
Keywords: twin pregnancy; birthweight; maternal outcomes; neonatal outcomes